CONSERVATION CONCEPT OF OLD KAMPUNG THROUGH THE APPLICATION OF SUSTAINABLE DEVELOPMENT PRINCIPLES AT KAMPUNG SURABAYAN, KEDUNGDORO DISTRICT, SURABAYA - Anindita Ramadhani; Erina Wulansari; Putri M. Mawarsari; Johan Silas (Journal of Architecture&ENVIRONMENT, 2014)
Kampung Surabayan is one of old kampungs in Surabaya, Indonesia, that has some potentials which can be developed as a sustainable kampung by balancing the environmental, socio-cultural, and economic aspects. In environmental aspect, Kampung Surabayan already has a good management based on various achievements from Green and Clean Competition (an eco-friendly settlement competition) and Safe Kampung Competition which held by Surabaya Government. The historical potential and cultural heritage, cooperative kampung’s residents, unique “kampung” traditions such as "cangkruk" or “free chattering” and "adu doro" or “pigeon racing”, carry social and culture values. Also, the green economy values that come from the resident’s creativity to manage domestic garbages into unique and valuable handicrafts.One aspect that still be left behind is heritage conservation. As an old kampung, Kampung Surabayan should be conserved in order to keep the authenticity of Kampung’s heritage. The potentials of Kampung Surabayan can be integrated by Heritage Tourism Concept to create a sustainable kampung heritage.